Bentuk Perbuatan Melawan Hukum Pelaku Pasif dalam Tindak Pidana Pembunuhan Berencana - Kartika, Tantri; Kartika , Tantri (Jurnal Hukum Ekualitas, 2025)
The form of crime against life that occurs in the community, for example the crime of premeditated murder in a community that has a different background or modus operandi in carrying out the premeditated murder, this premeditated murder is also carried out by people who according to reason and thought are not expected to be able to commit a premeditated murder crime. This crime of murder is not only carried out by someone who has deviant behavior or in other words who already has a background of someone who is naughty, evil, or a former convict who is already known to the community, but this premeditated murder crime can also be carried out by people who have good behavior in their community. The problem is what is the form of the unlawful act of the passive perpetrator in the act of premeditated murder. The research method is normative legal research. The form of unlawful act of the passive perpetrator in the act of premeditated murder is that the medepleger or person who participates in it is anyone who intentionally participates (medoet) in committing a crime. Passive perpetrators occur when the actions of each participant contain all the elements of a crime. In addition, the passive perpetrator in premeditated murder must require that the actions of the participating perpetrators must be the same as the actions of a perpetrator, his actions do not need to fulfill all the formulations of a criminal act, it is enough to fulfill only part of the formulation of a criminal act, as long as the intention is the same as the intention of the perpetrator.